PENGARUH KETERLIBATAN KARYAWAN DALAM IMPLEMENTASI MANAGEMENT BY OLIMPIC SYSTEM (MBOS) TERHADAP KINERJA KARYAWAN PADA PT INDAH KIAT PULP AND PAPER, TBK, PERAWANG - Frini Tiara Dwini; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of employee involvement in the implementation of management by olimpic system and employee performance partially. This study uses a questionnaire as a data collection tool that is distributed to 99 respondents at PT Indah Kiat Pulp and Paper, Tbk, Perawang employees. The data is then processed using descriptive analysis and statistical analysis using SPSS 22.0 by validating, reliability testing, simple linear regression analysis, determination analysis (R2) and hypothesis testing by t test (partial).The results showed that the hypothesis testing of employee involvement in the implementation of management by oklimpic system on employee performance is t count (6,342)> t table (1,984), meaning that the involvement of employees in the implementation of management by Olympic system (MBOS) has a significant effect on employee performance. Keywords: Employee Engagement, Management By Olympic System (MBOS), Employee Performance